Between Heaven and Earth: Places of Worship in Egypt and Syria through the Mirror of Visual Evidence - Rachel Sarfati (Arts, 2020)
In the villages Dammūh, near Fustֿׅatׅ, and Jobar, near Damascus, there were places of worship dedicated to Moses and Elijah which were part of central pilgrimage sites. This article will propose a depiction of the architecture and interiors of these places based on visual and literary sources from the Middle Ages. In addition to the realistic aspect, this article will suggest that the unique design of the reviewed illustrations expressed the prevalent belief that when the Temple was destroyed, the Shekhinah was exiled to the holy sites in Dammūh and Jobar. According to a common tradition, these places are located between heaven and earth, and he who prays in them feels like he is in the Garden of Eden.